Study of thick active region in a terahertz quantum-cascade laser - Sharma, Rajesh (Advanced Optical Technologies, 2025)
The research in the area of terahertz (THz) radiation is a subject of intense discussion in the international scientific community owing to its various applications in the fields of defense systems, security, interstellar studies, imaging, and agriculture. Although most of these applications have captured the attention of researchers in recent years, the development of a THz radiation source that meets specific requirements remains a challenging task. In this regard, the emission frequencies of terahertz quantum-cascade lasers (THz QCLs) can be fine-tuned by adjusting the thickness of the quantum well and the height of the barriers. The electron distribution among three periods of a hybrid active region design QCL structure is numerically simulated to estimate the optical gain spectra and electric field strength values. The results of the numerical simulations are compared with those of the experimental investigations by fabricating a 23 μm-thick active region THz QCL wafer by using the molecular beam epitaxy (MBE) technique. The wafer is split into six portions (A–F) to investigate the transport and the lasing properties. The electrical power dissipated at 10 K for the 23 μm-thick active region THz QCL stripe processed from the central portion (B) of the wafer is found to be approximately 56 W at the current density value of 0.53 kAcm−2. The thick active region THz QCL investigated in the present work operates in both pulsed and continuous-wave modes at the desired emission frequencies, which is a unique feature of the interlaced design. The optical output power of the 23 μm-thick active region THz QCL stripe compared to the 12 μm-thick active region is enhanced, attributed to improved mode confinement. Therefore, optimal performance in the pulsed mode can be achieved with thick active region THz QCL stripes fabricated near the center of the parent wafer. Nevertheless, thin active region THz QCLs are more suitable for continuous-wave operation due to reduced heat dissipation.